INTERPRETASI PERSEBARAN LAPISAN BATUBARA MENGGUNAKAN GEOPHYSICAL LOGGING PENDEKKATAN KRIGING DI PT. X, DAERAH PROVINSI KALIMANTAN TIMUR - Rahmayanti, Nur; Supriyanto, Supriyanto; Natalisanto, Adrianus Inu (GEOSAINS KUTAI BASIN, 2019)
Geophysical logging method is one of the geophysical methods used to determine thickness of the coal seam, the upper and the lower limits of the coal layer illustrate the lithology sequence of rocks in each borehole. The kriging method is one of the interpolation methods in geostatistical methods that often used to predict the problem. This study aims are determine the estimation of coal seam distribution derived from thickness data that obtained from the analysis of geophysical logging methods and the distribution of coal quality viewed from Ash content, Fixced Carbon, Volatile Matter, and Sulfur. The data used in this study are secondary data of coal weld data and coal quality data. Data from coal welding was analyzed using geophysical logging by considering the gamma ray log and log density to obtain coal thickness and then the coal thickness data. The coal quality data was used to estimate the distribution of coal layers and coal quality using the Ordenary Kriging method. Based on the results of the study. The NR4 seam coal is in the form of an estimation model which is displayed in color where there is a distribution of the thickness of the rock interpreted with the smallest coal thickness value of 0.7238 - 0.9055 (m) and the largest thickness value is 1,996 - 2,178 (m) with an average thickness 4,343 m and estimated ash content of 3,348% -11.7%, fixced carbon 40.72% - 46.22%, volatile matter 35.91% -39.49% and sulfur 0.152% - 0.981%.